THE DAILY PROFILE OF BLOOD PRESSURE IN METABOLIC SYNDROME: COMPARABLE ANALYSIS OF THE EFFICACY OF MONOTHERAPY WITH ENALAPRIL AND UNCONTROLLED ANTIHYPERTENSIVE THERAPY - M. N. Mamedov; V. M. Gorbunov; T. Sh. Dzahangirov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To assess an influence of ACE inhibitor enalapril on daily profile of blood pressure (BP) in comparison with uncontrolled antihypertensive therapy in patients with metabolic syndrome (MS). Material and methods. 41 patients with MS were included in opened parallel controlled study. Patients were randomized into two groups. Patients of the first group received enalapril (Enam, Dr. Reddy’s) 10 mg daily with the further titration of the dose up to 20 mg daily. Patients of the second group took previous antihypertensive therapy (15% of patients took ACE inhibitors, 15% - beta-blockers, 15% - diuretics and 20% - combined therapy). Study duration was 12 weeks.  Continuous ambulatory monitoring of BP (AMBP) was applied in all patients at the beginning and at the end of the study. Results. Enalapril therapy during 3 months in average dose of 17±1 mg daily reduced average 24-hour systolic, diastolic and pulse BP by 10, 8 and 14% respectively. These changes were significant in comparison with these in patients with uncontrolled therapy (3,7, 3,8 and 4% respectively). Enalapril reduced also average night systolic, diastolic and pulse BP (11, 11 and 10% respectively). In patients receiving uncontrolled therapy these changes were 3-4%. Two times decrease in BP burden in daytime and nighttime were observed while BP burden remained unchanged in uncontrolled therapy during both periods. Thanks to enalapril monotherapy a number of non-dippers reduced in more than two times due to recovering of night BP decrease (40% before and 15% after treatment). These changes were less expressive in the second group (45% before and 30% after treatment). Conclusion. Enalapril in average dose can be widely used for correction of daily BP profile in patients with MS.